Recalling gist memory depends on CA1 hippocampal neurons for lifetime retention and CA3 neurons for memory precision - Erika Atucha; Shih-Pi Ku; Michael T. Lippert; Magdalena M. Sauvage (Cell Reports, 2023)
Summary: Why some of us remember events more clearly than others and why memory loses precision over time is a major focus in memory research. Here, we show that the recruitment of specific neuroanatomical pathways within the medial temporal lobe (MTL) of the brain defines the precision of the memory recalled over the lifespan. Using optogenetics, neuronal activity mapping, and studying recent to very remote memories, we report that the hippocampal subfield CA1 is necessary for retrieving the gist of events and receives maximal support from MTL cortical areas (MEC, LEC, PER, and POR) for recalling the most remote memories. In contrast, reduction of CA3’s activity alone coincides with the loss of memory precision over time. We propose that a shift between specific MTL subnetworks over time might be a fundamental mechanism of memory consolidation.